2021
DOI: 10.11591/ijeecs.v24.i1.pp253-259
|View full text |Cite
|
Sign up to set email alerts
|

Attentional bias during public speaking anxiety revealed using event-related potentials

Abstract: <p>Analysis of brain signals and their properties provides valuable information regarding the underlying neural deficiencies and enables the diagnosis of attention bias related to public speaking anxiety (PSA). Although 25% people around the world suffer from PSA, currently, there exists a lack of standard assessment in diagnosing the severity of attention bias in individuals with PSA. This study aims to distinguish behavioral and neural abnormalities related to attentional bias during PSA by comparing r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Figure 2(a) shows that this effect is not apparent the HPSA group (HPSA neutral: 71.30886, 11.08138 ms, HPSA emotion: 73.36592, 11.71151 ms). The repeated measures ANOVA analysis showed non-significant σ differences between both groups (group×emotion effect) [𝐹 (1,22)=2.15296, partial ƞ 2 =0.089138, 𝑝=0.156447]. The emotional stimuli helped reduce typical RT variation, σ in the LPSA group, but not in the HPSA group, indicating impairment in the regulation of attention in the emotional condition in HPSA individuals [6].…”
Section: Ex-gaussian Analysis In the Emotional Stroop Experimentsmentioning
confidence: 96%
See 3 more Smart Citations
“…Figure 2(a) shows that this effect is not apparent the HPSA group (HPSA neutral: 71.30886, 11.08138 ms, HPSA emotion: 73.36592, 11.71151 ms). The repeated measures ANOVA analysis showed non-significant σ differences between both groups (group×emotion effect) [𝐹 (1,22)=2.15296, partial ƞ 2 =0.089138, 𝑝=0.156447]. The emotional stimuli helped reduce typical RT variation, σ in the LPSA group, but not in the HPSA group, indicating impairment in the regulation of attention in the emotional condition in HPSA individuals [6].…”
Section: Ex-gaussian Analysis In the Emotional Stroop Experimentsmentioning
confidence: 96%
“…Throughout the trials, participants were instructed to maintain their gaze on the monitor and keep their fingers positioned on the appropriate keypad buttons. Detailed information regarding the procedure of this study is illustrated in Figure 1 and could be found in [1].…”
Section: Task and Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…Broadcasters who are attractive and talented are those who not only have a beautiful facial appearance, but they must also have the intellectual ability to convey the material they present, improvise, and master language. The implementation of provision and understanding through the news anchor method is with the hope of developing personal potential, developing creativity in thinking, providing students with provisions for the future, and providing them with the ability to write news and convey information through news anchors (Feroz, 2021).…”
Section: A R T I C L E I N F Omentioning
confidence: 99%